13C-Metabolic flux analysis detected a hyperoxemia-induced reduction of tricarboxylic acid cycle metabolism in granulocytes during two models of porcine acute subdural hematoma and hemorrhagic shock - Wolfschmitt, Eva-Maria; Vogt, Josef Albert; Hogg, Melanie; Wachter, Ulrich; Stadler, Nicole; Kapapa, Thomas; Datzmann, Thomas; Messerer, David Alexander Christian; Hoffmann, Andrea; Gröger, Michael; Münz, Franziska; Mathieu, René; et al. (Frontiers in Immunology, 2024)
Supplementation with increased inspired oxygen fractions has been suggested to alleviate the harmful effects of tissue hypoxia during hemorrhagic shock (HS) and traumatic brain injury. However, the utility of therapeutic hyperoxia in critical care is disputed to this day as controversial evidence is available regarding its efficacy. Furthermore, in contrast to its hypoxic counterpart, the effect of hyperoxia on the metabolism of circulating immune cells remains ambiguous. Both stimulating and detrimental effects are possible; the former by providing necessary oxygen supply, the latter by generation of excessive amounts of reactive oxygen species (ROS). To uncover the potential impact of increased oxygen fractions on circulating immune cells during intensive care, we have performed a 13 C-Metabolic Flux Analysis (MFA) on PBMCs and granulocytes isolated from two long-term, resuscitated models of combined acute subdural hematoma (ASDH) and HS in pigs with and without cardiovascular comorbidity. By utilizing a parallel tracer approach with 1,2-13 C2 glucose, U-13 C glucose, and U-13 C glutamine, we covered essential pathways of glucose and glutamine metabolism and supplied redundant data for robust Bayesian estimation. Gas chromatography-mass spectrometry 2 This is a provisional file, not the final typeset article further provided multiple fragments of key metabolites which yielded additional labeling information. By applying this Bayesian 13 C-MFA model, we obtained precise estimations of the fluxes, their joint credibility intervals, and their relations, which indicated a hyperoxia-mediated reduction in tricarboxylic acid cycle activity in circulating granulocytes. We further detected elevated superoxide levels in the swine strain characterized by a hypercholesteremic phenotype as well as cell type-specific behavioral patterns of metabolic adaptation in response to ASDH and HS.